2007
DOI: 10.1111/j.1365-2796.2007.01890.x
|View full text |Cite
|
Sign up to set email alerts
|

Telomere attrition is associated with inflammation, low fetuin‐A levels and high mortality in prevalent haemodialysis patients

Abstract: . Introduction.  Chronic kidney disease (CKD) predisposes to a 10‐ to 20‐fold increased cardiovascular risk. Patients undergo accelerated atherogenesis and vascular ageing. We investigated whether telomere attrition, a marker of cell senescence, contributes to this increased mortality risk. Methods.  This is a cross‐sectional study in prevalent haemodialysis patients [n = 175; 98 Males; median (range) age: 66 (23–86) years]. Biochemical markers of oxidative stress and inflammatory status were measured in relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
157
2
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(170 citation statements)
references
References 47 publications
9
157
2
2
Order By: Relevance
“…Stress is transduced from the pregnant mother to her fetus through various pathways, including transplacental transport of the stress hormone cortisol, maternal stress-induced release of placental hormones that enter the fetal circulation (e.g., placental corticotrophin-releasing hormone), and maternal stress-induced effects on placental physiology, including alterations in blood flow and changes in metabolism impacting oxygen and glucose availability and use (52,53). Exposure to high levels of maternal stress hormones during pregnancy is known to produce deleterious effects on the offspring's developing immune system (32, 54, 55), and our previously published studies in this cohort have reported that the prenatally stressed individuals exhibited alterations in several immune parameters (33), including higher phytohemagglutinin-stimulated levels of IL-6, a proinflammatory cytokine that has been associated with shorter telomere length (56,57). We also have found that the prenatally stressed individuals in this cohort exhibited insulin and leptin resistance, as well as a higher BMI (31).…”
Section: Discussionmentioning
confidence: 72%
“…Stress is transduced from the pregnant mother to her fetus through various pathways, including transplacental transport of the stress hormone cortisol, maternal stress-induced release of placental hormones that enter the fetal circulation (e.g., placental corticotrophin-releasing hormone), and maternal stress-induced effects on placental physiology, including alterations in blood flow and changes in metabolism impacting oxygen and glucose availability and use (52,53). Exposure to high levels of maternal stress hormones during pregnancy is known to produce deleterious effects on the offspring's developing immune system (32, 54, 55), and our previously published studies in this cohort have reported that the prenatally stressed individuals exhibited alterations in several immune parameters (33), including higher phytohemagglutinin-stimulated levels of IL-6, a proinflammatory cytokine that has been associated with shorter telomere length (56,57). We also have found that the prenatally stressed individuals in this cohort exhibited insulin and leptin resistance, as well as a higher BMI (31).…”
Section: Discussionmentioning
confidence: 72%
“…Clinical studies have shown that total telomere shortening is associated with increasing chronological age (6,7), progression of arteriosclerosis (8,9), and CKD (10)(11)(12). Patients with CKD have a markedly increased risk for cardiovascular disease (CVD) (13) and total telomere shortening is associated with progression of CVD (14).…”
Section: Introductionmentioning
confidence: 99%
“…The length of telomeric DNA repeats shortens during the ageing of cultured somatic cells ( e.g. fibroblasts, peripheral blood lymphocytes and colon epithelia), but the rate of shortening is also under both polygenic and environmental influences (15,16). As a consequence, telomere length reflects the "miles on the clock" of a given individual or cell type.…”
Section: Telomeresmentioning
confidence: 99%